Effectiveness of Computerized Training Program to Develop Skills of Phonology Awareness to Activate Reading and Writing Abilities of a Sample of Talented Students with Learning Disabilities - Enas M. Oleimt (Sultan Qaboos University, 2018)
This study aimed to explore the effectiveness of a computerized training program to develop the skills of phonology awareness to activate the reading and writing abilities of a sample of talented students with learning disabilities. The sample consisted of 60 students in the school year 2015-2016. The researcher employed the Phonological and Articulation Disorders Scale (Oliemat and Al-Rosan, 2016) and the computerized training program of phonology awareness (Oliemat and Al-Fayez, 2012). Results revealed statisticaly significant differences in favor of the experimental group. Results also showed statisticaly significant differences in the posttest attributed to age in the phonology awareness level in favor of age category (8-9 years). The study recommended benefiting from these results when preparing remedial, educational, and training programs for students with various disabilities; conducting training programs on computerized software of phonology awareness; designing other computerized software for all types of phonological disorders and other ages of talented students with learning disabilities.